Exposure of Nursed Infants to Maternal Treatment with Ethambutol and Rifampicin. Issue 2 (14th April 2018) - Partosch, Falko; Mielke, Hans; Stahlmann, Ralf; Gundert‐Remy, Ursula
Abstract: Mycobacterial diseases remain a significant cause of morbidity and mortality worldwide. Rifampicin and ethambutol are among the drugs recommended by WHO as first‐line treatment. In this work, we addressed the question whether doses of the two anti‐tuberculosis agents ethambutol and rifampicin transferred to a nursed infant could be of health concerns when the mother is under treatment. We used the approach of pharmacokinetic modelling using a structural model with two interconnected organisms: the first one being the organism of the nursing mother and the second one being the organism of the nursed child. Physiological data were taken from the literature. The models were parameterised by data from the literature concerning clearance, absorption and plasma/milk ratio. Distribution into the tissues was calculated by an algorithm. The predictive power of the model was tested by comparing the predicted plasma concentrations in the mothers with measured data from the literature. Comparison with measured data after direct infant treatment was performed for the rifampicin plasma concentrations predicted in the nursed infant. Both comparisons confirmed the appropriateness of the modelling results. The transfer of 0.08 mg/kg bw/day ethambutol via breast milk to the nursed infant, the dose we have estimated, when the mother received a therapeutic dose of 24.5 mg/kg bw, can be judged as being without health concern. Likewise, for rifampicin, the transferred dose of 0.4 mg/kg bw to the nursed infant resulting from a therapeutic dose of 10.9 mg/kg bw to the mother does not raise health concerns.